Strand 1: Thesis and Antithesis on the use of Network Learning Technologies in Higher Education - Retalis, S.; Vescoukis, V. C.; Skordalakis, E. (Proceedings of the International Conference on Networked Learning, 1998)
There is a controversy on the use of network technologies in education especially at the undergraduate university level and below. This controversy stems from the conception of NLT’s implications in the social process: on the one hand, NLTs could be used as a cool to satisfy real social needs in culture, pedagogy and education, and to advance the social process; on the other hand, use of NLTs could be socially "blind" serving nothing but "technolove", producing generations with reduced or even bad social consciousness. This paper discusses these above issues using the schema thesis-antithesis introduced by ancient Greek philosophers, aiming to raise some sensitivity against the unconditional use of technology in Education.